PENINGKATAN MOTIVASI, AKTIVITAS DAN HASIL BELAJAR IPS MELALUI PENGGUNAAN MODEL TIPE STAD - Nurbaiti Nurbaiti; Sumadi Sumadi; Yon Rizal (Faculty of Teacher Training and Education, University of Lampung, 2015)
The purpose of this observation was determine the level of student motivation through model STAD application, find the model STAD in enhancing learning activities and determine the STAD model in increasing student learning outcomes. Data Collecting Technique in this research was using, test methods, and observation methods. Based on the analysis and discussion, it could be concluded that: Application of STAD cooperative learning model was by reporting the results of the group work in the group at standards of competency of knowing the social deviation, and understanding the factors that influence. The students application of STAD Cooperative learning model by giving different tasks for each group on the standarts of competency knowing the social deviation, and understanding the factors that influence. Application of STAD Cooperative learning model by giving different tasks for each group and report on the work in batches around between groups of standard of competency know the social deviation, and understanding the factors that influence the students.Tujuan penelitian untuk mengetahui peningkatan motivasi belajar siswa melalui peanerapan model pembelajaran STAD, mengetahui model pembelajaran STAD dalam meningkatkan aktivitas belajar dan mengetahui model pembelajaran STAD dalam meningkatkan hasil belajar siswa. Pengumpulan data dalam penelitian ini menggunakan metode tes, dan metode observasi. Berdasarkan analisis dan pembahasan, maka dapat disimpulkan bahwa: Penerapan model pembelajaran Cooperative tipe STAD dengan melaporkan hasil kerja kelompok secara berkeliling antar kelompok pada Standar Kompetensi mengenal penyimpangan sosial, pengertian dan faktor-faktor yang mempengaruhi siswa. Tugas yang berbeda untuk setiap kelompok pada Standar Kompetensi mengenal penyimpangan sosial, pengertian dan faktor-faktor yang mempengaruhi siswa. Penerapan model pembelajaran Cooperative tipe STAD dengan pemberian tugas yang berbeda untuk setiap kelompok dan melaporkan hasil kerja kelompok berkeliling antar kelompok pada Standar Kompetensi mengenal penyimpangan sosial, pengertian dan faktor-faktor yang mempengaruhi siswa.Kata kunci: aktivitas, hasil belajar ips, motivasi, stad